Allergen extract outperforms molecular components in basophil activation test in a pediatric cohort - Chhing, Alexandre; Choi, Simone; Khelifi-Touhami, Dounia; Abbas, Aïcha; Ballot, Eric; Cottel, Nathalie; Saf, Sarah; Germain, Garance; Lambert, Nathalie; Challier, Pierre; Pauliat, Sylvie; Lemoine, Anaïs; et al. (Frontiers in Immunology, 2026)
BackgroundThe use of molecular allergens have greatly improved the clinical relevance of specific IgE serologies during allergy work-up. Very little is known regarding the added value of molecular allergens in the results of the basophil activation test (BAT).ObjectiveTo study the BAT concordance when using similar amounts of molecular allergens against source extracts, and to assess factors associated with BAT discrepancies between extract and related component.MethodsSystematic retrospective monocentric study of all BAT performed at the Trousseau Hospital, Paris, France, with both molecular components and corresponding extract.ResultsData from 213 interpretable extract/component BAT pairs (89 cow milk, 70 wheat, 28 house dust mites (HDM), 12 peanut, 9 hen egg, 3 peach, 1 apple, 1 chicken meat), corresponding to 150 blood samples from 109 patients were analyzed. Among BAT pairs showing allergen sensitizations, the two reagents only showed moderate agreement (κ = 0.62), with 18% (36/201) discordant BAT results. Among 36 cases of discrepant BAT results between extract and molecular component, 69% (25/36) were extract+/component– (p=0.03), in line with genuine allergic status, in contrast with the opposite case. Even in extract+/component+ concordant cases, component-stimulated basophils showed 6% less activation rates than their extract-stimulated counterpart. After stratification by allergen, better performances were confirmed with cow milk extract, but not with other allergens, which display large disparity regarding the propensity of different molecular component to activate basophils. Independently of the considered allergen, other variables such as total IgE, BAT positive control values, and treatment with monoclonal antibody or allergen-specific immunotherapy, appear to further modulate the risk of presenting a discordant BAT result.ConclusionIn our study population, molecular components had lower capacity than the corresponding extract to activate IgE-sensitized basophils, which partly explain higher rates of true positive extract+/component– BAT. Component-based BAT can potentially lead to false-negative results, and extract-based should generally be preferred, especially for cow milk.